Access, Engagement and Resilience During COVID-19 Remote Learning - Bonella, Laura; Carroll, Doris; Jobe, Morgan; Kaff, Marilyn; Lane, Jessica; Martinez, Tonnie; McKeeman, Leah; Shuman, Cindy (Kansas State University, College of Education, 2020)
Kansas was the first state to close P-12 schools and move to a continuous learning model in response to the COVID-19 pandemic. A multidisciplinary group of K-State College of Education faculty researchers conducted a survey in May, 2020 to capture the voices and experiences of Kansas teachers, school counselors, and administrators during that time related to technology and broadband access, engagement and educator resiliency and self-care. Survey links were posted on the Remote Learning P-12 platform (https://remote-learning-p-12.mn.co/feed) and on the Kansas Educators Facebook group. These open links provided a sample of convenience, with 829 educators from across the state responding to the survey. The findings have implications for school districts, administrators, school counselors, teachers, and students in the coming school year. As schools begin to make decisions about what the current and critical needs are, three tenets must be addressed for optimal school re-entry: (1) Educator and student well-being, (2) Delivery models and high-quality instruction that are conducive and responsive to varied learning environments, and (3) School operations: Precautionary measures and logistics around COVID infection and contagion. This white paper provides data, insight, and recommendations in the areas of educator and student well being and delivery models.
Keywords: White Paper; COVID-19; Remote Learning; P-12 schools